2021
DOI: 10.1177/00328855211010407
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Emotional Literacy Programs on Inmates’ Empathy, Mindfulness, and Self-Regulation: A Random-Effect Meta-Analysis

Abstract: Applying a random-effect meta-analysis, the current study examines previous empirical findings about three main purposes of Emotional Literacy (EL) correctional programs: improving empathy, mindfulness, and self-regulation among inmate populations. A total of 22 programs in 15 studies in Germany, Portugal, the Netherlands, and the US are analyzed. Results suggest that EL programs significantly improve levels of empathy, mindfulness, and self-regulation, although a possibility of publication bias is observed. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…Produk yang akan dikembangkan digunakan untuk kelompok kecil. Berdasarkan studi literatur diungkapkan bahwa kelompok kecil dengan dipimpin fasilitator dan lingkungan yang mendukung hubungan antar peserta program diidentifikasi sebagai komponen penting suksesnya program (Choi & Back, 2021).…”
Section: Analisis Flashcard Sebagai Media Pelatihan Elunclassified
“…Produk yang akan dikembangkan digunakan untuk kelompok kecil. Berdasarkan studi literatur diungkapkan bahwa kelompok kecil dengan dipimpin fasilitator dan lingkungan yang mendukung hubungan antar peserta program diidentifikasi sebagai komponen penting suksesnya program (Choi & Back, 2021).…”
Section: Analisis Flashcard Sebagai Media Pelatihan Elunclassified
“…Qualitative work among couples welcoming a newborn shows that all of these elements (i.e., compromise, support, and mutual problem-solving) are an integral part of a positive parenting alliance after the birth of a child (Sheedy et al, 2019). The role of describing in the relationship between CCIT and parenting alliance could also translate into higher emotional literacy skills, which include both a greater capacity for recognizing personal feelings and empathy for the feelings of others (Petrosino et al, 2021). CCIT survivors who are better at identifying internal experiences could arguably detect those of their partner during interactions, potentially enhancing the quality of their parenting alliance.…”
Section: Distinct Roles Of Dispositional Mindfulness Facetsmentioning
confidence: 99%
“…It has also been found that emotional literacy affects individuals' well-being levels, making them happier individuals (Acton & Carter, 2016). The expanding literature also showed that emotional literacy was positively associated with self-efficacy (Malkoç & Aydın Sünbül, 2020), empathy, mindfulness, self-regulation (Petrosino et al, 2021), social competence, reduced behavioral problems, and decreased emotional distress (Kusché & Greenberg, 2012). Unfortunately, one study determined an inverse relationship between a lower than average level of emotional literacy and the likelihood of being victims of bullying among students (Harris, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional literacy refers to the ability to recognize, understand, and express one's own feelings and emotions and those of others (Sutton, 2023). According to Petrosino et al (2021), emotionally literate individuals are defined as individuals who are aware of their own emotions and those of the people they communicate with, use healthy emotion regulation methods, and have developed social skills by receiving support from the power of empathy. It has also been found that emotional literacy affects individuals' well-being levels, making them happier individuals (Acton & Carter, 2016).…”
Section: Introductionmentioning
confidence: 99%